2016
DOI: 10.1016/j.applanim.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental enrichment and composition of the social group on the behavior, welfare, and relative brain weight of growing rabbits

Abstract: Please cite this article in press as: Bozicovich, T.F.M., et al., Effect of environmental enrichment and composition of the social group on the behavior, welfare, and relative brain weight of growing rabbits. Appl. Anim. Behav. Sci. (2016), http://dx. a b s t r a c tThe objective of the study was to investigate if environmental enrichment and the composition of the social group would affect the behavior and relative brain weight of growing rabbits. Rabbits (72 males and 72 females) were assigned to cages with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 36 publications
(58 reference statements)
1
33
1
5
Order By: Relevance
“…Contrary to the studies outlining the welfare concerns of group housing rabbits, Bozicovich et al [ 9 ] found that group housed does within a commercial setting (that were provided with enrichment and grouped at 35 days old) demonstrated the lowest incidence of aggressive behavior. Mixed gender groups were shown to have an increased incidence of social interactions and a lower incidence of stereotypies [ 9 ]. This study advised, therefore, that mixed gender groups should be housed collectively from weaning at four weeks of age.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to the studies outlining the welfare concerns of group housing rabbits, Bozicovich et al [ 9 ] found that group housed does within a commercial setting (that were provided with enrichment and grouped at 35 days old) demonstrated the lowest incidence of aggressive behavior. Mixed gender groups were shown to have an increased incidence of social interactions and a lower incidence of stereotypies [ 9 ]. This study advised, therefore, that mixed gender groups should be housed collectively from weaning at four weeks of age.…”
Section: Discussionmentioning
confidence: 91%
“…An appropriately enriched environment (including basic necessities for this species such as the provision of hides, items to chew on and to investigate, and open areas to run and hop) have a significant effect on welfare, as well as the behavior demonstrated between group housed individuals. For example, in a laboratory setting, provision of enrichment within a farmed rabbit setting in the form of wooden sticks to chew lead to a lower incidence of skin injuries, which could be extrapolated to pet rabbits [ 9 ]. Mullan and Main [ 4 ] suggest that the human–rabbit bond may also be strengthened with access to an enriched environment and human contact.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different enrichments, gnawing materials are most commonly used. In growing rabbits kept in cages and pens with both small (2–4 animals/cage) and medium-size (13–15 animals/pen) groups, gnawing sticks have often reduced stereotyped behaviors, such as cage bar biting or chewing [10,11], aggressive interactions [12], skin wounds [13], and ear lesions [14]. On the other hand, some studies have not found a significant reduction of abnormal behaviors [15], whereas others have reported an increase of aggressive behavior when gnawing materials were provided [13].…”
Section: Introductionmentioning
confidence: 99%
“…A possibility to enrich the rabbits’ environment is to provide them with different materials, such as gnawing sticks. These were observed to reduce aggressive behavior [11,15], injuries [10,11,39] and abnormal behaviors such as bar gnawing [40,41,42,43]. Some authors also found a positive impact of wooden sticks on daily weight gain and slaughter weight [40], and temporarily higher daily weight gain in enriched pens with a platform, hiding box and gnawing material [44].…”
Section: Introductionmentioning
confidence: 99%